Наймання пастуха на Слобожанщині у II половині XIX – на початку XXI століть - Маліков, Василь Володимирович (Харківський національний університет ім. В. Н. Каразіна, 2008)
The significance of the hire of cattleman in the existence of ways of cattle pasturing, customary law ideas and social life of Slobidska Ukraine peasantry is studied in this paper. The analysis of ethnographic sources of the II half of XIX – beginning of XXI centuries has made possible to find out main trends of changes of traced phenomenon and their influence on farming, social relations, socialization, traditional beliefs and ideas of peasantry
Keywords: випас; соціалізація; звичаєве право; пастух